2023
DOI: 10.3390/jof9020211
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Isavuconazole in Critical Care Patients with COVID-19-Associated Pulmonary Aspergillosis and Monte Carlo Simulations of High Off-Label Doses

Abstract: Isavuconazole is a triazole antifungal agent recently recommended as first-line therapy for invasive pulmonary aspergillosis. With the COVID-19 pandemic, cases of COVID-19-associated pulmonary aspergillosis (CAPA) have been described with a prevalence ranging from 5 to 30%. We developed and validated a population pharmacokinetic (PKpop) model of isavuconazole plasma concentrations in intensive care unit patients with CAPA. Nonlinear mixed-effect modeling Monolix software were used for PK analysis of 65 plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 56 publications
1
20
0
2
Order By: Relevance
“…None of these factors were relevant for our patient's isavuconazole Pk, and were excluded in our compartmental model. Although isavuconazole oral administration seems to be better studied by bi-compartimental model, previous publications agreed with our mono-compartmental model in intravenous administration [19]. Moreover, Perez et al´s model only found CRRT as a signi cant covariant for isavuconazole Pk in 18 critically ill patients [19].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…None of these factors were relevant for our patient's isavuconazole Pk, and were excluded in our compartmental model. Although isavuconazole oral administration seems to be better studied by bi-compartimental model, previous publications agreed with our mono-compartmental model in intravenous administration [19]. Moreover, Perez et al´s model only found CRRT as a signi cant covariant for isavuconazole Pk in 18 critically ill patients [19].…”
Section: Discussionsupporting
confidence: 83%
“…Although there is no total consensus about the normal range in isavuconazole trough concentrations, most authors accept a range between 1 and 5 mg/L [3,[19][20][21]. Population pharmacokinetic parameters were performed from the plasma concentrations obtained and using the computer software NONMEN® (v.5) implementing a rst-order conditional estimation method with interaction (ADVAN 1, TRANS 2).…”
Section: Isavuconazole Pharmacokineticmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have analysed isavuconazole drug levels in different patient populations or with specific risk factors. Whereas numerous of those support the use of routine TDM of isavuconazole, 15,16 some reports question this measure, 17 but acknowledge its value under specific circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Regarding the influence of RRT on isavuconazole levels, a study with seven solid-organ transplant patients reported no rapid removal by RRT, 34 while others found an association between RRT and sub-therapeutic levels of the drug. 15,16,30,35 The role of adsorptive membranes has been related to lowered maximal concentrations of echinocandins, which are similarly lipophilic like isavuconazole. 36 Therefore, the adsorption of isavuconazole to the synthetic surfaces of hemofilters could contribute to the decreased drug levels in RRT patients.…”
Section: Discussionmentioning
confidence: 99%